A Security Perspective on International Migration - Weiner, Myron (Tufts Archival Research Center, 2005)
Volume 20, Issue 2. Summer/Fall Migratory flows, which are often the result of deliberate state policies, can create conflicts within and between states. Myron Weiner examines migration as a threat to the security and stability of both sending and receiving countries.